Comparative anatomical study of leaf tissues of scab resistant and susceptible apple cultivars - Varga, D.; Udvardy, L. (International Journal of Horticultural Science, 2010)
According to previous studies some anatomical features seem to be connected with resistance or susceptibility to scab caused by Venturia ineaqulis (Cke./Wint.) in case of a given cultivar. Study of leaf anatomy of three scab resistant (‘Prima’, ‘Florina’, MR–12) and two susceptible (‘Watson Jonathan’, ‘Golden Delicious Reinders’) apple cultivars have been made. Preserved preparations made of leaves has been studied by light microscope. Studied parameters were: thickness of leaf blade, thickness of palisade and spongy parenchyma, thickness of epidermal cells, thickness of the cuticle. By measuring leaf thickness and epidermal cell thickness visible differences appeared in certain cultivars, while most conspicuous difference has been shown in thickness of the cuticle.